Characterization of the Stability of Indium Tin Oxide and Functional Layers for Semitransparent Back‐Contact Applications on Cu(in, Ga)Se2 Solar Cells. Issue 7 (6th May 2022) - Fonoll-Rubio, Robert; Placidi, Marcel; Hoelscher, Torsten; Thomere, Angelica; Li-Kao, Zacharie Jehl; Guc, Maxim; Izquierdo-Roca, Victor; Scheer, Roland; Pérez-Rodríguez, Alejandro
Abstract : Herein, a detailed study of the stability of different ITO‐based back‐contact configurations (including bare ITO contacts and contacts functionalized with nanometric Mo, MoSe2, and MoS2 layers) under the coevaporation processes developed for the synthesis of high‐efficiency Cu(In, Ga)Se2 (CIGSe) solar cells is reported. The results show that bare ITO layers can be used as efficient back contacts for coevaporation process temperatures of 480 ºC. However, higher temperatures produce an amorphous In–Se phase at the ITO surface that reduces the contacts transparency in the visible region. This is accompanied by degradation of the solar cells' efficiency. Inclusion of a Mo functional layer leads to the formation of a MoSe2 interfacial phase during the coevaporation process, which improves the cells' efficiency, achieving device efficiencies similar to those obtained with reference solar cells fabricated with standard Mo back contacts. Optimization of the initial Mo layer thickness improves the contact transparency, achieving contacts with an optical transparency of 50% in the visible region. This is accompanied by a relevant decrease in back reflectivity in the CIGSe devices, confirming the potential of these contact configurations for the development of semitransparent CIGSe devices with improved optical aesthetic quality without compromising the device performance. Abstract : A study of the stability of ITO‐based back contacts during CIGS synthesis is reported. For processing temperatures higher than 480 °C, an amorphous phase is formed at the surface of bare ITO, accompanied with degradation of transparency and device performance. Inclusion of a nanometric functional layer (and thickness optimization) allows to improve both parameters at high‐temperature processing.